2016
DOI: 10.1007/s10157-016-1343-z
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in septic acute kidney injury in critically ill children: a cohort of post-mortem renal biopsies

Abstract: The most common renal histopathological change in septic AKI in critically ill children was normal histology followed by ATN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Other well-known contributors for AKI as invasive mechanical ventilation and hemodynamic instability could not be evaluated as they were common denominators in our population (7,(29)(30)(31). To be noticed, we found 91.8% of ATI, 49.4% being moderate to severe, similar to other COVID-19 studies with 70.6%-100%; contrary to this, in patients who are septic, some reports account for 20%-30% of ATI (32,33). In this sense, the coparticipation of cytokine storm, nephrotoxic medication, and, possibly, a deeper and more prolonged hypoxia contributing to hypoperfusion could explain the higher incidence of ATI, without taking into account any direct viral-contributing action so far.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other well-known contributors for AKI as invasive mechanical ventilation and hemodynamic instability could not be evaluated as they were common denominators in our population (7,(29)(30)(31). To be noticed, we found 91.8% of ATI, 49.4% being moderate to severe, similar to other COVID-19 studies with 70.6%-100%; contrary to this, in patients who are septic, some reports account for 20%-30% of ATI (32,33). In this sense, the coparticipation of cytokine storm, nephrotoxic medication, and, possibly, a deeper and more prolonged hypoxia contributing to hypoperfusion could explain the higher incidence of ATI, without taking into account any direct viral-contributing action so far.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical data are provided in Supplemental Table 1. Median age was 57 (50-67) years, 59 (69%) were men, body mass index was 29 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) kg/m 2 , 43 (51%) had diabetes, and 39 (46%) had chronic hypertension. All patients required invasive mechanical ventilation, 70 (82%) received vasopressors, 83 (98%) were treated with anticoagulants (43% prophylactic and 53% therapeutic dose), 56 (66%) were treated with steroids, and 30 (35%) received at least one potential nephrotoxic medication.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Surprisingly, we found no association between low levels of antithrombin and kidney failure or underlying kidney disease. Other studies in adults have clearly shown that antithrombin may help limit acute kidney injury ( Yin et al., 2017 ; Kong et al., 2017 ; Wang et al., 2015 ; Rameshkumar et al., 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated the occurrence of both tubular necrosis and apoptosis in sepsis-induced AKI (21,22). The study of Takasu et al presented histological evidence for a low incidence of tubular necrosis in sepsis, with a rare instance of apoptosis in kidney tissue as detected by staining for cleaved cytokeratin-18 (23).…”
Section: Discussionmentioning
confidence: 99%